Inclusive Leadership in Improving Employee Performance - Heriyana (Yayasan Pendidikan Belajar Berdikari, 2024)
This research investigates the relationship between inclusive leadership style, training and employee performance in MSMEs. Data was collected from respondents who are employees of various companies in MSMEs, using quantitative methods with survey techniques and statistical analysis. The results of the analysis show that the model studied has a good level of fit (R-squared = 0.508), indicating that the research variables are able to explain most of the variation in employee performance. The correlation between inclusive leadership style and training (r = 0.574), inclusive leadership style and performance (r = 0.737), and training and performance (r = 0.582) shows a significant positive relationship between these variables. The T test shows that both inclusive leadership style (T count = 5.754) and training (T count = 3.710) have a significant influence on employee performance, with a T value that exceeds the specified T table value. In addition, the F test confirms that partially, all research variables have a significant influence on employee performance (F count = 75.320). In conclusion, inclusive leadership style and training play a crucial role in improving employee performance in MSMEs. These findings provide the implication that leadership development that trains and pays attention to inclusive leadership styles can be an effective strategy for improving employee performance in the MSME context.